HUBUNGAN MOTIVASI BELAJAR DENGAN PRESTASI BELAJAR SISWA DI SD 28 BUNGIN LAREH NAN PANJANG BARAT - Nurhasnah, Nurhasnah; Usman , Usman; Nurva Dillatul Vatin; M. Hubbal Khair (Affection: Journal of Psychology And Counseling, 2025)
This research is motivated by the low motivation of students to learn, which is an important factor in learning success. Success can be achieved if there is a strong motivation from within the student, because motivation functions as a driver to achieve good achievement, while lack of motivation can reduce learning achievement. This study aims to determine the level of student learning motivation, the level of student learning achievement, and the relationship between learning motivation and student learning achievement at SDN 28 Bungin Lareh Nan Panjang Barat. The approach used is quantitative with the research subjects of grade IV, V, and VI students totaling 41 students. Data were collected through a learning motivation questionnaire and documentation of learning achievement, using a questionnaire measuring tool based on the theory of Amanillah & Rosiana (2017). Data analysis using Pearson correlation test. The results showed that the sig value (2-tailed) was 0.000 <0.05, which means there is a significant relationship between learning motivation and learning achievement. The correlation coefficient of 0.530 shows that the relationship between the two variables is 53.0% and is positive, with t count (3.936) > t table (1.685), so it can be concluded that the higher the learning motivation, the higher the student learning achievement, and vice versa.